Safeguarding in dance as a public health issue: a systems-level policy framework - Jennifer Cumming; Mary L. Quinton (Frontiers in Public Health, 2026)
Safeguarding in dance is an under-recognized public health policy issue, characterized by inconsistent implementation and limited regulation. Drawing on public health frameworks, we conceptualize safeguarding-related harms through a biopsychosocial lens, encompassing physical, psychological, and social impacts. These harms are shaped by interacting factors across individual, interpersonal, organizational, and structural levels. The absence of systemic surveillance and regulatory oversight limits prevention, early intervention, monitoring, and evaluation of safeguarding practices. We propose six complementary policy actions: national surveillance systems, safeguarding audits, a quality mark, clear reporting frameworks, funding-linked accountability, and trauma- and violence-informed care. Together, these actions provide a coordinated, systems-level response, improving accountability, and promoting safe, healthy, and more equitable dance participation.